Epistemology and Language of Science Fiction - Paronyan, Sushanik; Muradian, Gaiane (Bulletin of Yerevan University B: Philology, 2023)
Background knowledge plays an important role in understanding and appreciating both visual and literary creations. As society becomes more knowledgeable, more mature, technologically more advanced, and more sophisticated, the knowledge required to appreciate arts, including verbal art, increases greatly. In the comprehension of science fiction (SF), equal to reading experience, a substantial degree of background knowledge is needed to perceive the narrative and the plot devices, properly appreciate the informative and the aesthetic aspects of the discourse, and contemplate its consequences. This background knowledge challenging human intellect in SF is based on epistemology – the theory and construction of knowledge and the study of knowledge acquisition addressing cognitive sciences, involving an awareness of certain aspects of reality and seeking to discover what is known and how it is known. Moreover, in its relation to SF, epistemology explains why our minds relate to reality and how these relationships are either valid or invalid. Hence, the results of the present study based on case study, extrapolative and linguostylistic methods of investigation, show that epistemology helps to distinguish between the truth and falsehood as we obtain knowledge from the world around us and, in this case, from such a literary genre as SF.